Interlaboratory comparison of six real-time PCR assays for detection of bovine leukemia virus proviral DNA - Jaworski, Juan Pablo (2018)
Quantitative real-time PCR (qPCR) is increasingly being used for the detection of bovine leukemia virus (BLV) proviral DNA. Nevertheless, quality control for the validation and standardization of such tests is currently lacking. Therefore, the present study was initiated by three Office International des Epizooties (OIE) reference laboratories and three collaborating laboratories to measure the interlaboratory variability of six already developed and available BLV qPCR assays. For that purpose, an international panel of 58 DNA samples reflecting the dynamic range of the majority of the assays was distributed to six testing centers. Based on qualitative results, the overall agreement among all six laboratories was moderate. However, significant variability in the measurement of the BLV proviral DNA copy number was observed among different laboratories. Quantitative PCR assays, even when performed by experienced staff, can yield large variability in BLV proviral DNA copy numbers without harmonization. Further standardization of different factors (i.e., utilization of unified protocols and unique calibrators) should increase interlaboratory agreement.